Application of nanomolybdenum in beans and its impact on nitrogen efficiency - Muñoz-Márquez, Ezequiel; Soto-Parra, Juan Manuel; Pérez-Leal, Ramona; Yánez-Muñoz, Rosa María; Noperi-Mosqueda, Linda Citlalli; Sánchez-Chávez, Esteban (Revista Mexicana de Ciencias Agrícolas, 2022)
The efficient use of nitrogen is a technique used to improve yields without the excessive addition of nitrogen fertilizers, in the same way, the use of nanofertilizers is an alternative to solve nutritional problems with greater efficiency and precision, both with the purpose of increasing crop productivity. Therefore, the objective of this study was to evaluate the foliar application of molybdenum (Mo) nanofertilizer combined with the edaphic fertilization of NH4NO3, on the total biomass, yield and efficiency in snap beans. The plants were germinated and grown under controlled conditions in an experimental greenhouse in Lázaro Cárdenas, Meoqui, Chihuahua, Mexico in September 2020 and irrigated with nutrient solution. The treatments consisted of the foliar application of four doses of the molybdenum nanofertilizer BROADACRE (0, 5, 10 and 20 ppm of Mo), complemented by the edaphic application of four doses of nitrogen in the form of NH4NO3 (0, 3, 6 and 12 mM of N). The results obtained indicate that the doses of 10 ppm of Mo and 6 mM of N favored the accumulation of biomass and the highest yield per plant; it is important to note that the highest efficiency was achieved with the doses of 5 ppm of Mo and 3 mM of N. Finally, it is concluded that the application of NanoMo increases the efficiency of nitrogen use, being able to reduce excessive applications of nitrogen fertilizers, without affecting the yield of snap beans.